Desarrollo de una plataforma en wolfram mathematica para evaluar perfiles de concentración y temperatura en la saponificación del acetato de etilo - Lomas Valles, Deisy Steffany (2023)
The main objective of the present work of thesis was: developing a platform in Wolfram Mathematica to evaluate profiles of concentration and temperature in the reaction of saponification of ethyl acetate. For that matter a mathematical model that represents the reaction of saponification of ethyl acetate was deduced, getting oneself a bibliographic revision on the programming language of Wolfram Mathematica and the equation of balance molar once a semi-continuous reactor was applied. The equations that create said mathematical model programmed in Wolfram Mathematica themselves. The results of the simulation of the mentioned mathematical model, show that the concentration of the ethyl acetate inside the reactor, he decreases its value from 5 kmol/m3 in, ?? = 0 s even in ?? = 300 s. The concentration of the sodium hydroxide inside the reactor, increases from 0 kmol/m3 in ?? = 0 s, even 0.0197385 kmol/m3 in v ?? = 250 s and from them, begin to increase even 0.268293 kmol/m3 in ?? = 360 s. The concentration of the sodium acetate inside the reactor, increases from 0 kmol/m3 in ?? = 0 s, even 0.813595 kmol/m3 in ?? = 250 s and from them, begin to diminish even 0.609756 kmol/m3 in ?? = 360 s. In this way is coming true with the objective general and trying on his general hypothesis.